2022
DOI: 10.1615/intjinnovonlineedu.2022044659
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in Crisis: Student Self-Efficacy and the Online Pivot

Abstract: The COVID-19 outbreak required a pivot to remote education mid-semester. Instructors and students alike were forced to adjust to the online platform even though many lacked the training or interest to do so. This qualitative study focused on the following research question: How did satellite campus students from a university in the United States perceive their educational experience was affected by the alternative educational offerings put into place during the COVID-19 campus closure of March 2020? The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Reilly et al (2021) found that WP students were less confident about asking their instructors for help as compared to their peers, which aligns with MacKay et al's (2021) work on WP students using lecture capture to help navigate asking for help. In context of covid, self-efficacy may have suffered from having fewer opportunities to experience vicarious success due to reduced interaction with peers (whether real or imagined), as well as a more negative emotional state (Garner et al, 2022). Students from disadvantaged backgrounds and minority groups report lower self-efficacy (Satici & Can, 2016) and so taken together, there is evidence to support the idea that the WP experience of online learning during covid may have compounded the challenges these students face.…”
Section: Theoretical Approaches To Widening Participationmentioning
confidence: 99%
“…Reilly et al (2021) found that WP students were less confident about asking their instructors for help as compared to their peers, which aligns with MacKay et al's (2021) work on WP students using lecture capture to help navigate asking for help. In context of covid, self-efficacy may have suffered from having fewer opportunities to experience vicarious success due to reduced interaction with peers (whether real or imagined), as well as a more negative emotional state (Garner et al, 2022). Students from disadvantaged backgrounds and minority groups report lower self-efficacy (Satici & Can, 2016) and so taken together, there is evidence to support the idea that the WP experience of online learning during covid may have compounded the challenges these students face.…”
Section: Theoretical Approaches To Widening Participationmentioning
confidence: 99%